The moth catcher eaudiobook - Cleeves, Ann (Vera Stanhope, 2016)
From Ann Cleeves comes The Moth Catcher , the latest audiobook in the Vera Stanhope mystery series, the inspiration behind the hit TV series, Vera . Life seems perfect in the quiet community of Valley Farm. Then a shocking discovery shatters the silence. The owners of a big country house have employed a house-sitter, a young ecologist, to look after the place while they're away. But his dead body is found by the side of the lane—a lonely place to die. When DI Vera Stanhope arrives on the scene, she finds the body of a second man. What the two victims seem to have in common is a fascination with studying moths—and with catching these beautiful, intriguing creatures. The others who live in Valley Farm have secrets too: Lorraine's calm demeanor belies a more complex personality; Annie and Sam's daughter, Lizzie, is due to be released from prison; and Nigel watches, silently, every day, from his window. As Vera is drawn into the claustrophobic world of this increasingly strange community, she realizes that there may be many deadly secrets trapped there . . .